Analisis Pembiayaan Umrah di Amitra Syariah Financing Banjarnegara menurut Fatwa DSN-MUI No. 44/DSN-MUI/VIII/2004 tentang ljärah Multijasa - Lutfi Ziddan Fahriza (Program Studi Hukum Ekonomi Syariah, 2026)
Amitra Syariah Financing is a sharia financial institution that provides Umrah financing based on DSN-MUI Fatwa No. 44/DSN-MUI/VIII/2004 concerning Multi-Service Ijārah. In practice, Amitra purchases Umrah packages from travel agencies and hands them over to customers with a minimum down payment of 15%, while the remainder is paid in installments over 12, 24, or 36 months. This study aims to analyze the conformity of Umrah financing practices with the Sharia principles in the fatwa. The study used a qualitative method with a field research approach through interviews, observations, and literature studies. The results show that Umrah financing at Amitra has fulfilled the pillars of the multi-service Ijārah contract, including the existence of contracting parties, service objects, sighat contract, and ujrah. However, the determination of ujrah based on the principal financing and the length of the installment tenor has the potential to contain elements of qardh and riba nasi’ah so that it is not fully in accordance with Sharia principles. The novelty of this research lies in its critical analysis of the ujrah (price) determination mechanism in multi-service ijarah-based umrah financing at non-bank Islamic financing institutions. The study's weakness is its limitation to a single research object, making the results unable to be broadly generalized to other Islamic financing institutions.